Mpox and oral health among children in Africa - Foláyan, Moréniké Oluwátóyìn; Ishola, Adeyinka Ganiyat; Bhayat, Ahmed; El Tantawi, Maha; Sam-Agudu, Nadia Adjoa; Ndembi, Nicaise (Frontiers in Oral Health, 2025)
Much like it has historically, recent mpox outbreaks in Africa have significantly affected children and highlight major public health challenges, including oral healthcare in pandemic responses. The global 2022 outbreak saw an unprecedented number of mpox cases outside Africa, however children were a minority, constituting less than 2%, with the vast majority of cases reported among adult men who have sex with men. However, African countries continue to report high proportions of pediatric mpox cases, particularly Clade 1 in Burundi, the DRC, and the Congo, and Clade 2 in Nigeria. Oral manifestations of mpox such as ulcers and lesions on the lips and tongue are common and can precede skin rash, making early diagnosis challenging, especially in low-resource settings. Misdiagnosis is also a risk due to the similarity of mpox oral lesions to common pediatric exanthems and enanthems. Oral and other manifestations so mpox among affected children in Africa may be worsened due to delayed treatment and increased morbidity from high rates of malnutrition and immunosuppression, including due to HIV. This paper explores the implications of mpox on the oral health of children in Africa, emphasizing the need for improved surveillance, early detection, and the integration of the mpox response into existing child health programs. Child-focused clinical and public health research, healthcare worker training, and accessible, child-friendly diagnostic tools will be crucial for mitigating the impact of mpox on this vulnerable population.